Thermodynamic evaluation of solar integration into a natural gas combined cycle power plant. (February 2015) - Zhu, Guangdong; Neises, Ty; Turchi, Craig; Bedilion, Robin
Abstract: The term integrated solar combined-cycle (ISCC) has been used to define the combination of solar thermal energy into a natural gas combined-cycle (NGCC) power plant. Based on a detailed thermodynamic cycle model for a reference ISCC plant, the impact of solar addition is thoroughly evaluated for a wide range of input parameters such as solar thermal input and ambient temperature. It is shown that solar hybridization into an NGCC plant may give rise to a substantial benefit from a thermodynamic point of view. The work here also indicates that a significant solar contribution may be achieved in an ISCC plant, thus implying substantial fuel savings and environmental benefits. Highlights: Examine thermodynamic benefits of Integrated Solar Combined-Cycle (ISCC). Examine solar conversion efficiency under varying solar heat and ambient conditions. Solar addition can boost steam cycle efficiency. Solar conversion efficiency is higher than steam cycle efficiency in the ISCC plant.